Wood Polymer Nanocomposites Chemical Modifications, Properties and Sustainable Applications - Rahman, Md Rezaur (Engineering Materials,, 2018)
This book shows how chemical modifications influence some properties of wood nanocomposites. It describes suitable and effective chemical modifications that strengthen the physico-mechanical, thermal and morphological properties of wood. The authors provide intuitive explanation of the various types of chemical modifications applied to polymer cell walls in wood. They emphasize the reaction changes in wood cell walls due to the chemical modifications. Increased mechanical strength, improved thermal stability as well as the efficient retardancy against fungi attack are described. This book concludes summarizing the potential applications of wood-based nanocomposites taking into account sustainability and economic aspects.